Metallographic and Magnetic Properties of Allan Hills 762 Iron Meteorite - Fisher, R.M.; Spangler, C.E.Jr.; Nagata, Takesi; Funaki, Minoru (1979)
P(論文) Allan Hills 762 a 1.5kg iron meteorite from West Antarctica, contains 7.2% Ni, 0.6% Co, and 0.4% P, and is identified as a very coarse octahedrite from its chemical and metallographic properties. According to WASSON, its genetic classification is group IAB, similar to Neptune Mountain also found in the Antarctic. Magnetic and metallographic analyses revealed that the structure is primarily well-annealed kamacite of 6.4% Ni with a small amount of comb plessite, grain boundary schreibersite, and numerous rhabdite particles. Two very unusual microstructural features were observed. Many of the narrow taenite bands contain small pools of kamacite in what may be termed a very coarse plessite structure which apparently formed during prolonged heating at moderate temperatures of about 450℃. All phosphide, (FeNi)_3P, particles are surrounded by a narrow ragged rim of taenite. A possible mechanism for the occurrence of those previously unobserved structures is proposed. departmental bulletin paper